Conceptual Bases of Fundamental Research of Structure and Content of the Specializations «Artistically-Project Creation», «Decoratively-Applied Art», «Bases of Design» of the Profile Teaching in the National System of Continuous Artistically-Project Educa - Vdovychenko, Viktor; Antonovych, Yevhen (Pedagogical Discourse, 2015)
In the article the attention is accented on the native changes for years of independence of Ukraine that took place in engineering, designer, artistically-project education, since pre-university - profile preparation in general educational establishments (GEE). The substantive provisions of conceptual bases of fundamental research of structure and content of the specializations «Artistically-Project Creation», «Decoratively-Applied Art», «Bases of Design» of the profile teaching in the national system of continuous artistically-project education have been determined. The ways of solving of the problem of providing by the teaching-methodological complete sets of the noted specializations of the profile GEE have been shown. The question of the scientifically grounded stage-by-stage introduction to the educational process of profile GEE of artistically-project education have been reflected. For the first time, after transition to the competence result of profile preparation, modern scientific source base for introduction of new concept-terminology apparatus of the profile teaching of the national system of continuous artistically-project education have been offered.